2014
DOI: 10.1039/c3ra47244b
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent density functional study of UV-visible absorption spectra of small noble metal clusters (Cun, Agn, Aun, n = 2–9, 20)

Abstract: Absorption UV-visible spectra of noble metal clusters Cu n , Ag n , Au n , n = 2−9 and 20, are investigated in the framework of the time-dependent density functional theory (TDDFT) using the long-range corrected density functionals LC-M06L and CAM-B3LYP and high-quality gaussian basis sets. Some calculations including the spin-orbit coupling are also presented. The contribution of the d electrons to the optical response is found to be lower than it is when a purely local exchange functional is used. Calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 64 publications
4
46
0
Order By: Relevance
“…In summary, the comparison between observed and simulated absorption spectra demonstrates that (i) the Ne matrix does not qualitatively influence the structure and electron dynamics in Au 20 , and (ii) the generally fair agreement between TDDFT predictions (including the previous literature 42 ) and experiment makes us confident in using a TDDFT approach also for investigating fluorescence phenomena. For technical reasons, we are only able to do this at the TDDFT/B3LYP scalar-relativistic (SR) level on the two low-energy α and β absorption peaks.…”
Section: B Dft and Tddft Modeling And Comparison With Experimentsmentioning
confidence: 84%
See 2 more Smart Citations
“…In summary, the comparison between observed and simulated absorption spectra demonstrates that (i) the Ne matrix does not qualitatively influence the structure and electron dynamics in Au 20 , and (ii) the generally fair agreement between TDDFT predictions (including the previous literature 42 ) and experiment makes us confident in using a TDDFT approach also for investigating fluorescence phenomena. For technical reasons, we are only able to do this at the TDDFT/B3LYP scalar-relativistic (SR) level on the two low-energy α and β absorption peaks.…”
Section: B Dft and Tddft Modeling And Comparison With Experimentsmentioning
confidence: 84%
“…Previous theoretical work showed that the position and intensity of predicted absorption peaks of Au 20 are rather sensitive to the theoretical approach employed, especially the xc-functional. 42 Local density or gradient-corrected xc-functionals severely underestimate the intensity of absorption peaks below 3 eV, and a proper description of the Coulombic tail of the potential is crucial to assure a reasonable description of the optical response of Au clusters. 42 Neglecting the moment spin-orbit (SO) effects, TDDFT/B3LYP predicts absorption peaks below 3 eV at 2.22 eV, 2.42 eV, and 2.88 eV, and three major peaks between 3.08 and 3.39 eV towering the spectrum (see Table S1 of the supplementary material for more information and an analysis of the excited states in terms of single-particle components).…”
Section: B Dft and Tddft Modeling And Comparison With Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 The long-range corrected xc functional LC-ωPBEh 33 is used in order to accurately recover the asymptotic behaviour of the exchange correlation potential, since this has proven to reliably reproduce vertical electronic excitation spectra. 4,6,8,24,33,34 The theoretical description of optical properties of clusters based on TDDFT calculations is easily applicable and widely used, in particular due to the low computational costs associated with the single-reference character. 42 In minimizations the BP-86 43,44 and M06-L 45 functionals are also studied for comparison purposes.…”
mentioning
confidence: 99%
“…As the most "alkali-like" group-11 element, it has been well studied in a number of theoretical investigations, 1-3 especially due to the strong surface plasmon absorption in the visible regime observed in silver clusters and nanoparticles. [4][5][6][7][8][9]52 In order to understand the size-dependent physical and chemical properties of such nano-sized silver particles, small clusters consisting of only a few atoms are ideal model systems. [10][11][12][13] The relatively large s-d separation means that the optical response is mainly associated with selectrons while d-electrons are only partially involved in the excitations.…”
mentioning
confidence: 99%